Implementasi Program Literasi Digital Untuk Penanggulangan Kenakalan Remaja di Nagari Panyakalan - Jusra, Yana Maulidia; Adi, Isbandi Rukminto (Jayapangus Press, 2026)
This research implements the Stringer Action Research framework to address juvenile delinquency through digital literacy in Nagari Panyakalan. The research analyzes the implementation process, strategies, and dynamics of the digital literacy program, as well as identifies supporting and inhibiting factors during the Act stage. Using a qualitative approach with Stringer's cyclical method (Look, Think, Act), the study focuses on the Act stage. Data were collected through participatory observation, in-depth interviews, and focus group discussions. Findings indicate that the Action phase, realized through the